The mediating role of fear of childbirth in the relationship between intolerance of uncertainty and cesarean section preference among pregnant women - Zhang, Feng; Zan, Yuqing; Liu, Min; Hu, Shanshan; Zhou, Ningying; Zhang, Wenjing; Wang, Na (Frontiers in Psychiatry, 2026)
ObjectiveThis study aims to investigate the relationship between intolerance of uncertainty and preference for cesarean section, and to explore whether fear of childbirth mediates the relationship between intolerance of uncertainty and preference for cesarean section.MethodsA total of 310 pregnant women in the third trimester who attended outpatient clinics at Wuxi Maternal and Child Health Hospital from July to September 2024 were included in this study. The survey instruments used included a Sociodemographic Information Questionnaire, Intolerance of Uncertainty Scale-12, and the Fear of Birth Scale. Mediation analysis was conducted using R 4.4.3 software.ResultsA total of 310 surveys were distributed to participants, and ultimately 290 eligible questionnaires were collected, resulting in a response rate of 93.55%. The prevalence of cesarean section preference among participants was 20.69%. The mean score for intolerance of uncertainty was 30.94 ± 7.13, and the mean score for fear of childbirth was 51.50 ± 23.32. This study shows that intolerance of uncertainty and fear of childbirth are both positively associated with a preference for cesarean section. Fear of childbirth mediates the relationship between intolerance of uncertainty and preference for cesarean section.ConclusionsIntolerance of uncertainty is a positive predictor of preference for cesarean section, and fear of childbirth mediates this association. These findings provide a basis for developing targeted interventions to reduce rates of unnecessary cesarean sections.